High Definition Television: New Perceptual Cognitive and Aesthetic Challenges (Vol20, No. 2, 1991) - Metallinos, Nikos (Canadian Journal of Learning and Technology, 2009)
This is a reprinted version of an article in Vol. 20 No. 2. You can view the original here.